Preparation method of temperature-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer
By using coal-based graphene oxide as the filter loss reducer for drilling fluid, the problems of traditional filter loss reducer are solved, with large thickness, high cost and poor biodegradability of filter cakes, small filter loss, thin filter cake thickness, and environmental protection. Efficient drilling fluid performance.
Patent Information
- Application Number
- CN202411447859.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional drilling fluid filter loss agents have problems such as large thickness, high cost and poor biodegradability of the filter cake, making it difficult to effectively control the filtration loss and protect the well wall.
Coal-based graphene oxide is used as the filter loss reducer. By adding thickening agent, sodium chloride, calcium chloride and dispersant to the water, a mixture of coal-based graphene oxide dispersion and mixed thickening solution is formed to achieve drilling fluid. filter loss effect.
It has achieved small filtration loss and thin filter cake thickness, which has little harm to the reservoir, reduced formation damage and well wall instability, and has low production costs and good biodegradability, which meets the requirements of green and environmental protection.
Smart Images

Figure HDA0005088215280000011 
Figure HDA0005088215280000012 
Figure HDA0005088215280000013
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nanomaterials and drilling fluids, and in particular to a method for preparing a temperature-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer. Background Art
[0002] In the process of oil and gas drilling, drilling fluid plays a vital role as a key engineering fluid. The main functions of drilling fluid include cooling and lubricating the drill bit, carrying cuttings, preventing wellbore collapse and controlling formation pressure. During the drilling process, the water in the drilling fluid will inevitably penetrate into the formation through the wellbore wall, and the solid particles will adhere to the wellbore wall to form a filter cake. The formation of the filter cake not only prevents the drilling fluid from losing water further, but also protects the wellbore wall. The control of filtration loss and filter cake thickness is of great significance to maintaining the performance of drilling fluid and ensuring the smooth progress of drilling operations. Excessive filtration loss and filter cake thickness will not only lead to a decrease in wellbore stability, but may also cause a series of complex problems such as formation damage and drill bit jamming, affecting the normal construction and development efficiency of oil and gas wells.
[0003] In order to reduce the amount of fluid loss, fluid loss additives are widely used in drilling projects. These materials effectively prevent water in the drilling fluid from entering the formation by forming a low-permeability filter cake. However, traditional fluid loss additives, such as bentonite, starch, carboxymethyl cellulose, etc., have certain limitations. Although these materials have a good fluid loss reduction effect, the filter cakes they form are often thicker, which affects the stability of the wellbore and drilling efficiency. Although some synthetic polymer material fluid loss additives have superior performance, they are expensive and have poor biodegradability, which easily causes environmental pollution and does not conform to the development trend of green environmental protection. Therefore, it is of great practical significance to develop an efficient and environmentally friendly fluid loss additive. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a temperature-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer. The preparation method of the present invention has simple steps, obvious filtrate reduction effect, little harm to the reservoir, and can realize industrial production, which is helpful to promote the green and efficient exploitation of oil and gas.
[0005] To achieve the above object, the technical solution of the present invention comprises the following steps:
[0006] Step 1, adding 0.25% to 1% of the weight of a thickener into water, stirring at high speed while heating, and keeping the water warm to fully dissolve the thickened solution;
[0007] Step 2, adding 5% to 10% of sodium chloride and 1% to 5% of calcium chloride by mass of the thickened solution to the thickened solution, stirring thoroughly to dissolve them, and then adding 1% to 5% of a dispersant to obtain a mixed thickened solution;
[0008] Step 3, adding 0.4% to 1% by weight of coal-based graphene oxide into water to disperse and obtain a coal-based graphene oxide dispersion;
[0009] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed to make the mixture evenly mixed, and let it stand for 1 to 2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid loss reducer.
[0010] The thickening agent in step 1 includes one or more of xanthan gum, carboxymethyl cellulose, polyacrylamide, sesbania gum, guar gum, flax gum, fenugreek gum, and modified starch.
[0011] The heating temperature of step 1 is 40-95° C., and the insulation time is 1-2 hours.
[0012] The high-speed stirring speed in step 1 and step 4 is 1000-2000 rpm.
[0013] The dispersant in step 2 is a carboxylated polyether polymer.
[0014] The dispersion method in step three is ultrasound, mechanical stirring or a combination thereof.
[0015] The coal-based graphene oxide in step three has a size of 100 nm to 5 μm, with an average size of 800 nm.
[0016] The coal-based graphene oxide in step three has an average number of layers of 1 to 2 layers and a thickness of 0.6 to 2.2 nm.
[0017] The coal-based graphene oxide of the present invention has good flexibility, and the oxygen-containing functional groups on its surface can interact with other components in the drilling fluid (such as high molecular polymers, natural colloids, etc.) through hydrogen bonds and van der Waals forces. These intermolecular forces make the filter cake formed by the coal-based graphene oxide on the well wall more compact and stable, thereby effectively improving the filtration control effect and preventing the filtrate of the drilling fluid from penetrating into the formation. The coal-based graphene oxide drilling fluid filtration reducer prepared according to the above method has a small filtration loss, a thin filter cake thickness, and little damage to the reservoir, which helps to promote green and efficient oil and gas exploitation.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The coal-based graphene oxide of the present invention has a unique two-dimensional nanosheet structure and rich oxygen-containing functional groups, which enable it to form a denser and more uniform filter cake on the well wall, effectively preventing drilling fluid from penetrating into the formation, reducing formation damage, and improving well wall stability.
[0020] (2) The preparation method of the present invention utilizes coal resources as raw materials and prepares coal-based graphene oxide through optimized process technology. Compared with traditional graphene or other high-performance fluid loss reducers, the production cost is significantly reduced, which is conducive to large-scale industrial applications and improves economic benefits. At the same time, it has good biodegradability and meets the requirements of sustainable development.
[0021] (3) The coal-based graphene oxide fluid loss reducer of the present invention is not only suitable for conventional drilling, but also can maintain stable performance in complex formation environments such as high salt and high calcium. It has wide applicability and can meet the needs of various drilling conditions.
[0022] (4) The coal-based graphene oxide of the present invention has a higher specific surface area and surface activity than traditional materials, and can achieve a significant filtration control effect at a lower addition amount, thereby reducing the amount of filtration reducer used and optimizing the drilling fluid formula. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 a is the XRD spectrum of coal-based graphene oxide prepared in Example 1 of the present invention;
[0024] Figure 1 b is the Raman spectrum of the coal-based graphene oxide prepared in Example 1 of the present invention;
[0025] Figure 1 c is the C1s spectrum of the coal-based graphene oxide XPS prepared in Example 1 of the present invention;
[0026] Figure 2 a is a SEM image of coal-based graphene oxide prepared in Example 1 of the present invention;
[0027] Figure 2 b is a TEM image of coal-based graphene oxide prepared in Example 1 of the present invention;
[0028] Figure 2 c is the size statistics of coal-based graphene oxide prepared in Example 1 of the present invention;
[0029] Figure 3 a is an AFM image of coal-based graphene oxide prepared in Example 1 of the present invention;
[0030] Figure 3 b is Figure 3 The height curve of the line AB in a;
[0031] Figure 3 c is the height statistics of coal-based graphene oxide prepared in Example 1 of the present invention;
[0032] Figure 4 a is a dynamic filtration loss curve of the coal-based graphene oxide fresh water slurry prepared in Example 1 of the present invention through API standard filter paper;
[0033] Figure 4 b is the final filtration loss and filter cake thickness of the coal-based graphene oxide freshwater slurry prepared in Example 1 of the present invention through the API standard filter paper;
[0034] Figure 5 a is the cross-sectional SEM image of the filter cake formed by 4% bentonite on API filter paper in fresh water-based slurry;
[0035] Figure 5 b, c are cross-sectional SEM images of filter cakes formed on API filter paper with 1% coal-based graphene oxide in fresh water-based slurry;
[0036] Figure 6 a is a dynamic filtration loss curve of the coal-based graphene oxide fresh water slurry prepared in Example 1 of the present invention through a filter paper with a pore size of 0.1 μm;
[0037] Figure 6 b is the final filtration loss and filter cake thickness of the coal-based graphene oxide freshwater slurry prepared in Example 1 of the present invention through a filter paper with a pore size of 0.1 μm;
[0038] Figure 7 Optical photographs of coal-based graphene oxide prepared in Example 2 of the present invention dispersed in water, brine, and brine / dispersant;
[0039] Figure 8 a is a dynamic filtration loss curve of the coal-based graphene oxide salt water-based slurry prepared in Example 2 of the present invention through API standard filter paper;
[0040] Figure 8 b is the final filtration loss and filter cake thickness of the coal-based graphene oxide salt water-based slurry prepared in Example 2 of the present invention through the API standard filter paper;
[0041] Fig. 9 a is a SEM image of the filter cake surface formed by coal-based graphene oxide prepared in Example 2 of the present invention passing through API standard filter paper in fresh water-based slurry;
[0042] Fig. 9 b is a SEM image of the filter cake surface formed by the coal-based graphene oxide prepared in Example 2 of the present invention passing through API standard filter paper in a salt water-based slurry;
[0043] Fig. 9 c is a SEM image of the filter cake surface formed by the coal-based graphene oxide prepared in Example 2 of the present invention passing through API standard filter paper in a salt water-based slurry with a dispersant added;
[0044] Fig.10 a is a dynamic filtration loss curve of the coal-based graphene oxide salt water-based slurry prepared in Example 2 of the present invention through a filter paper with a pore size of 0.1 μm;
[0045] Fig.10 b is the final filtration loss and filter cake thickness of the coal-based graphene oxide salt water-based slurry prepared in Example 2 of the present invention through a filter paper with a pore size of 0.1 μm;
[0046] Fig.11 a is a SEM image of the 0.1 μm pore size filter membrane used in Example 2 of the present invention;
[0047] Fig.11 b is a SEM image of the coal-based graphene oxide fluid loss reducer prepared in Example 2 of the present invention when forming a filter cake;
[0048] Fig.12 a is a dynamic filtration loss curve of the coal-based graphene oxide salt water-based slurry prepared in Example 3 of the present invention through API standard filter paper at 70° C.;
[0049] Fig.12 b is the final filtration loss and filter cake thickness of the coal-based graphene oxide salt water-based slurry prepared in Example 3 of the present invention through the API standard filter paper at 70° C.;
[0050] Fig.13 a is a dynamic filtration loss curve of the coal-based graphene oxide salt water-based slurry prepared in Example 3 of the present invention passing through a filter paper with a pore size of 0.1 μm at 70° C.;
[0051] Fig.13 b is the final filtration loss and filter cake thickness of the coal-based graphene oxide salt water-based slurry prepared in Example 3 of the present invention through a 0.1 μm pore size filter paper at 70°C. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0053] Embodiment 1:
[0054] Step 1, adding a thickening agent xanthan gum to water and heating it to 90° C., stirring at a high speed of 1000-2000 rpm, and keeping the temperature for 1 hour to fully dissolve it to obtain a thickened solution with a mass concentration of 0.36%;
[0055] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0056] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickening solution are 5%, 1% and 2% respectively;
[0057] Step 3, adding coal-based graphene oxide to water and mechanically stirring and dispersing to obtain a coal-based graphene oxide dispersion with a mass concentration of 5%;
[0058] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0059] The filtration loss of the freshwater-based slurry through the API standard filter paper and the 0.1 μm pore size filter paper was tested using a medium pressure filter loss meter, API standard filter paper and 0.1 μm pore size filter paper; the filter cake was removed, and its thickness was tested using a thickness gauge after the filter cake was dried.
[0060] Embodiment 2:
[0061] Step 1, adding a thickening agent xanthan gum to water, heating to 95° C., stirring at a high speed of 1000-2000 rpm, and keeping warm for 1.5 hours to fully dissolve it to obtain a thickened solution with a mass concentration of 0.37%;
[0062] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0063] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickened solution are 9.6%, 2.4% and 1.7% respectively;
[0064] Step 3, adding coal-based graphene oxide to water and ultrasonically dispersing to obtain a coal-based graphene oxide dispersion with a mass concentration of 2%;
[0065] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0066] The filtration loss of the water-based drilling fluid through the API standard filter paper and the 0.1 μm pore size filter paper was tested using a medium pressure filter loss meter, API standard filter paper and 0.1 μm pore size filter paper; the filter cake was removed, and its thickness was tested using a thickness gauge after the filter cake was dried.
[0067] Embodiment 3:
[0068] Step 1, adding a thickener xanthan gum to water and heating it to 85°C, stirring at a high speed of 1000-2000 rpm, and keeping the temperature for 2 hours to fully dissolve it to obtain a thickened solution with a mass concentration of 0.36%;
[0069] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0070] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickened solution are 9.8%, 2.6% and 2.1% respectively;
[0071] Step 3, adding coal-based graphene oxide to water and mechanically stirring and dispersing to obtain a coal-based graphene oxide dispersion with a mass concentration of 2%;
[0072] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0073] The salt water-based slurry was heated to 70°C, and the filtration loss of the water-based drilling fluid through API standard filter paper and 0.1 μm pore size filter paper was tested using a medium pressure filter loss meter; the filter cake was removed, and after the filter cake was dried, its thickness was tested using a thickness gauge.
[0074] Embodiment 4:
[0075] Step 1, adding a thickening agent guar gum to water and heating it to 50° C., stirring at a high speed of 1000-2000 rpm, and keeping the temperature for 1 hour to fully dissolve it to obtain a thickened solution with a mass concentration of 0.33%;
[0076] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0077] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickened solution are 9.9%, 2.6% and 2.3% respectively;
[0078] Step 3, adding coal-based graphene oxide to water and ultrasonically dispersing to obtain a coal-based graphene oxide dispersion with a mass concentration of 3%;
[0079] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0080] The salt water-based slurry was heated to 90°C, and the filtration loss of the water-based drilling fluid through API standard filter paper and 0.1 μm pore size filter paper was tested using a medium pressure filter loss meter; the filter cake was removed, and after the filter cake was dried, its thickness was tested using a thickness gauge.
[0081] Embodiment 5:
[0082] Step 1, adding a thickening agent, carboxymethyl cellulose, to water, heating to 40° C., stirring at a high speed of 1000-2000 rpm, and keeping the temperature for 1.5 hours to fully dissolve it to obtain a thickening solution with a mass concentration of 0.5%;
[0083] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0084] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickening solution are 6%, 3% and 4% respectively;
[0085] Step 3, adding coal-based graphene oxide to water and ultrasonically dispersing to obtain a coal-based graphene oxide dispersion with a mass concentration of 3%;
[0086] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0087] Embodiment 6:
[0088] Step 1, adding a thickener polyacrylamide to water, heating to 80°C, stirring at a high speed of 1000-2000 rpm, and keeping warm for 2 hours to fully dissolve it to obtain a thickened solution with a mass concentration of 0.7%;
[0089] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0090] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickening solution are 7%, 5% and 1.5% respectively;
[0091] Step 3, adding coal-based graphene oxide to water and mechanically stirring and dispersing to obtain a coal-based graphene oxide dispersion with a mass concentration of 4%;
[0092] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0093] Embodiment 7:
[0094] Step 1, adding a thickener, sesbania gum, to water, heating to 60° C., stirring at a high speed of 1000-2000 rpm, and keeping the temperature for 2 hours to fully dissolve the water to obtain a thickened solution with a mass concentration of 0.25%;
[0095] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0096] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickening solution are 8%, 2% and 3.5% respectively;
[0097] Step 3, adding coal-based graphene oxide to water and ultrasonically dispersing to obtain a coal-based graphene oxide dispersion with a mass concentration of 5%;
[0098] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0099] Embodiment 8:
[0100] Step 1, adding a thickening agent modified starch to water, heating to 70° C., stirring at a high speed of 1000-2000 rpm, and keeping warm for 1 hour to fully dissolve it to obtain a thickened solution with a mass concentration of 0.8%;
[0101] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0102] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickening solution are 9%, 4% and 3% respectively;
[0103] Step 3, adding coal-based graphene oxide to water, and dispersing by mechanical stirring to obtain a coal-based graphene oxide dispersion with a mass concentration of 3.5%;
[0104] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0105] Embodiment 9:
[0106] Step 1, adding a mixture of thickener guar gum and carboxymethyl cellulose to water, heating to 85° C., stirring at a high speed of 1000-2000 rpm, and keeping warm for 2 hours to fully dissolve the mixture to obtain a thickened solution with a mass concentration of 1%;
[0107] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0108] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickening solution are 10%, 1.5% and 5% respectively;
[0109] Step 3, adding coal-based graphene oxide to water, and dispersing by mechanical stirring to obtain a coal-based graphene oxide dispersion with a mass concentration of 2.5%;
[0110] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0111] Embodiment 10:
[0112] Step 1, adding a mixture of thickener xanthan gum, carboxymethyl cellulose and polyacrylamide to water, heating to 75° C., stirring at a high speed of 1000-2000 rpm, and keeping warm for 1, 1.5, 2, and 1-2 hours to fully dissolve the mixture to obtain a thickened solution with a mass concentration of 0.6%;
[0113] Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant carboxylated polyether polymer to obtain a mixed thickened solution;
[0114] The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickening solution are 6.5%, 3.5% and 2% respectively;
[0115] Step 3, adding coal-based graphene oxide to water, and ultrasonically dispersing to obtain a coal-based graphene oxide dispersion with a mass concentration of 4.5%;
[0116] Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed of 1000-2000 rpm to make the mixture evenly mixed, and let it stand for 1-2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid filtrate reducer.
[0117] Example 1 Experimental part:
[0118] 1. Phase structure and composition characterization of coal-based graphene oxide
[0119] Figure 1 a shows the XRD spectrum of coal-based graphene oxide. It can be observed that the characteristic diffraction peak of graphene oxide appears at 9.5°. According to the Bragg equation λ=2dsinθ, its interplanar spacing can be calculated to be about 0.9nm, which is much larger than the standard interlayer spacing of graphite 0.3354nm. This is because the introduction of oxygen-containing groups such as carboxyl and hydroxyl groups causes the adjacent single-layer graphite carbon layers to be peeled off and the interplanar spacing increases. Figure 1 b shows the Raman spectrum of coal-based graphene oxide.-1 The D peak at 1580 cm represents the defects of carbon materials. -1 The G peak at represents the ordered lattice structure of the carbon material. Since graphene oxide itself introduces oxygen-containing groups to cause lattice distortion and twisting, the corresponding D peak intensity is higher, reflecting the defects inside coal-based graphene oxide. Figure 1 c shows the C1s spectrum of coal-based graphene oxide XPS. The peak at 284.2 eV corresponds to C=C, which corresponds to the sp 2 structural domain; the peaks at 285.9 eV, 287.4 eV and 288.7 eV correspond to CO, C=O and OC=O, respectively, which means that there are oxygen-containing groups such as hydroxyl, carboxyl and epoxy groups in coal-based graphene oxide.
[0120] 2. Characterization of coal-based graphene oxide morphology
[0121] Figure 2 The SEM image of a shows coal-based graphene oxide sheets distributed on a silicon wafer, and its size statistics are shown in Figure 2 In c, the size span is relatively large, with the smallest being only nanometers and the largest being over 4 μm. Figure 2 The TEM image in b clearly shows the wrinkles of coal-based graphene oxide, reflecting the flexibility of coal-based graphene oxide, which is a typical feature of single-layer graphene oxide.
[0122] Figure 3 a is the AFM image of coal-based graphene oxide. By observing its contrast, it can be seen that the coal-based graphene oxide sheet is very thin; Figure 3 b is Figure 3 The height curve of the AB line in a shows that its thickness is about 2nm. The height of coal-based graphene oxide was further statistically analyzed, and the results are as follows: Figure 3 As shown in c, the thickness is distributed in the range of about 0.6 to 2.2 nm, and the thickness is about 1 to 2 layers.
[0123] 3. Performance evaluation of coal-based graphene oxide fluid loss additive in fresh water-based slurry
[0124] Figure 4 a shows the dynamic filtration loss curve of bentonite and coal-based graphene oxide under API filter paper. The final filtration loss of 4% bentonite under API standard filter paper in 30 minutes is 17.4mL, and the filtration loss of 0.4% coal-based graphene oxide is 22.8mL, which is higher than the filtration loss of bentonite. Further increasing the concentration of coal-based graphene oxide to 1.0%, the filtration loss in 30 minutes is reduced to 14.4mL. The filter cake was placed at room temperature for 12 hours, and its thickness was measured using a thickness gauge after it was dried. Figure 4b shows the final filtration loss and filter cake thickness comparison of bentonite and coal-based graphene oxide under API filter paper. It can be seen that the use of coal-based graphene oxide as a filtration reducer can reduce both the filtration loss and filter cake thickness. Figure 5 As shown in a and b, the filter cake thickness decreased by 49% compared with 4% bentonite, from 153.9 μm to 78.2 μm. Figure 5 c Further magnification and observation of the cross-section of the coal-based graphene oxide filter cake show that the layered structure formed by the stacking of coal-based graphene oxide can be observed.
[0125] Considering the existence of a large number of nanopores in the formation and the unevenness of the pore size, 0.1 μm filter paper was also used to carry out the above experiment. Figure 6 a shows the dynamic filtration loss curve of bentonite and coal-based graphene oxide at a pore size of 0.1 μm. The filtration loss of 0.4% coal-based graphene oxide is 18.6 mL, which is very close to the filtration loss of 4% bentonite, 18.4 mL. This may be related to Figure 2 The coal-based graphene oxide shown in a has a submicron size. Figure 6 As shown in (b), the filter cake thickness of coal-based graphene oxide at a pore size of 0.1 μm decreased more significantly than that at the pore size of API filter paper, decreasing by 78% from 144.8 μm to 32.2 μm, indicating that coal-based graphene oxide may have greater potential in reducing filtration loss in nanopores.
[0126] Example 2 Experimental part:
[0127] 1. Performance evaluation of coal-based graphene oxide fluid loss additive in salt water-based slurry
[0128] In drilling operations, especially in deep wells or high-pressure oil and gas formations, a large amount of salts (such as sodium chloride, potassium chloride, etc.) are often added to the drilling fluid to adjust the density of the drilling fluid, inhibit the hydration expansion of the formation mud shale, and control the stability of the wellbore. However, the interaction between salt ions and fluid loss reducer molecules may change the structure and performance of the fluid loss reducer. For coal-based graphene oxide, salt ions will shield the charge on the coal-based graphene oxide sheets, resulting in a decrease in its dispersibility in the solution. Therefore, in order to ensure the normal use of coal-based graphene oxide, it is necessary to solve the problem of its difficulty in dispersing in salt water. Figure 7 The following are photos of graphene oxide dispersion in water, 1M CaCl2 solution, and 1M CaCl2 solution with dispersant added. Graphene oxide has negative charges due to the presence of a large number of carboxyl groups (-COOH) and hydroxyl groups (-OH) at the edges of its sheets. Negative charges repel each other, making graphene oxide well dispersed in water. However, in CaCl2 salt water, due to the presence of Ca 2+They will gather on the surface of GO sheets, shielding these negative charges and reducing the electrostatic repulsion between sheets, thus agglomerating. After adding a dispersant to the salt water, the steric hindrance effect brought by the dispersant prevents the graphene oxide from agglomerating and is evenly dispersed in the salt water. Figure 8 a is the dynamic filtration loss curve of coal-based graphene oxide in salt water. From the figure, we can see that the filtration loss of 0.4% coal-based graphene oxide in salt water is lower than that in fresh water. This may be due to the effect of salt ions that make the submicron coal-based graphene oxide aggregate and assemble, forming a denser filter cake. However, due to the agglomeration of coal-based graphene oxide caused by this charge shielding, the thickness of the filter cake increases significantly. Fig. 9 The SEM image of the filter cake shows that the filter loss in fresh water can form a smooth filter cake with a thickness of only 30.6 μm, while in salt water, due to the agglomeration of coal-based graphene oxide, the filter cake surface is uneven ( Fig. 9 b), and its thickness also increased sharply to 133.0 μm. For this reason, we added a dispersant to eliminate or weaken its agglomeration phenomenon. After adding the dispersant, its filtration loss was reduced to 14.0 mL, and its SEM image showed a smooth and flat surface again ( Fig. 9 c) We believe that the dispersant can effectively alleviate the stacking of graphene oxide, significantly improving the effect of reducing filtration loss. At the same time, the filter cake thickness is only 59.0μm, which is 56% lower than the filter cake of brine without dispersant ( Figure 8 b).
[0129] The 0.1 μm filter paper was also used to evaluate the filtration loss reduction effect of coal-based graphene oxide on submicron pores in salt water. Fig.10 As shown in a and b, the trend is roughly the same as that under API filter paper. The filtration loss of coal-based graphene oxide in brine is 17.0 mL. The addition of dispersant reduces the filtration loss to 11.4 mL, and the filter cake thickness is reduced from 88.2 μm to 49.4 μm.
[0130] In addition, the filter cake at the beginning of formation was characterized by SEM, such as Fig.11 As shown in a and b. Fig.11 a is the surface morphology of the 0.1 μm filter membrane, where a large number of fibers are densely interwoven to form nanopores; Fig.11 Figure b shows the morphology of the filter cake at the beginning of its formation on the filter membrane surface. A clear translucent film covers many fibers, which reduces the filtration loss by increasing the path for the movement of water molecules.
[0131] Example 3 Experimental part:
[0132] Finally, in order to simulate the actual working conditions, 0.4% coal-based graphene oxide and 4% bentonite commonly used in oilfield operations were selected for high temperature and high salt tests. The two base slurries were heated to 70°C and kept warm for 1 hour to test their filtration control effects. Fig.12 shown. Fig.12 a is the dynamic filtration loss of coal-based graphene oxide filtrate reducer under API filter paper. At 1 min, the filtration loss of coal-based graphene oxide is 4.8 mL, which is greater than 3.0 mL of 4% bentonite. At 7.5 min, the filtration loss of coal-based graphene oxide is equal to that of bentonite, and gradually becomes lower than that of bentonite. This may be because the average size of coal-based graphene oxide is relatively small, and it cannot instantly block the 2.7μm pores of API filter paper, resulting in a large initial filtration loss rate. Subsequently, the coal-based graphene oxide forms a dense filter cake with a lower filtration rate than bentonite, and the final filtration loss is also lower than bentonite. And in Fig.13 In a, since the pore size of the filter paper is 0.1 μm, coal-based graphene oxide can instantly have a good plugging effect on the pores, and its filtration loss is always lower than that of bentonite. Fig.12 b and 13b show the final filtration loss and filter cake thickness comparison of coal-based graphene oxide and bentonite on API filter paper and 0.1μm filter paper, respectively. Whether it is micropore or nanopore, the filtration loss control effect of coal-based graphene oxide is far better than that of bentonite, especially in terms of filter cake thickness. The filter cake thickness of coal-based graphene oxide is reduced by 60% and 77% compared with bentonite, respectively, proving its great potential as a drilling fluid loss reducer in the oil field.
Claims
1. A method for preparing a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer, characterized in that: The following steps are involved: Step 1, adding a thickener to water, stirring at high speed while heating, and keeping the water warm to fully dissolve the thickener to obtain a thickened solution with a mass concentration of 0.25% to 1%; Step 2, adding sodium chloride and calcium chloride to the thickened solution, stirring them thoroughly to dissolve them, and then adding a dispersant to obtain a mixed thickened solution; The mass concentrations of sodium chloride, calcium chloride and dispersant in the mixed thickening solution are 5-10%, 1%-5% and 1%-5% respectively; Step 3, dispersing coal-based graphene oxide in water to obtain a coal-based graphene oxide dispersion having a mass concentration of 2% to 5%; Step 4: Mix the coal-based graphene oxide dispersion and the mixed thickening solution in a mass ratio of 1:4, stir at a high speed to make the mixture evenly mixed, and let it stand for 1 to 2 hours to stabilize it to obtain a heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid loss reducer.
2. The method for preparing the heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer according to claim 1, characterized in that: The thickening agent in step 1 includes one or more of xanthan gum, carboxymethyl cellulose, polyacrylamide, sesbania gum, guar gum, flax gum, fenugreek gum, and modified starch.
3. The method for preparing the heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer according to claim 1, characterized in that: The heating temperature of step 1 is 40-95° C., and the insulation time is 1-2 hours.
4. The method for preparing the heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer according to claim 1, characterized in that: The high-speed stirring speed in step 1 and step 4 is 1000-2000 rpm.
5. The method for preparing the heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer according to claim 1, characterized in that: The dispersant in step 2 is a carboxylated polyether polymer.
6. The method for preparing the heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer according to claim 1, characterized in that: The dispersion method in step three is ultrasound, mechanical stirring or a combination thereof.
7. The method for preparing the heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer according to claim 1, characterized in that: The coal-based graphene oxide in step three has a size of 100 nm to 5 μm, with an average size of 800 nm.
8. The method for preparing the heat-resistant and salt-resistant coal-based graphene oxide water-based drilling fluid fluid loss reducer according to claim 1, characterized in that: The coal-based graphene oxide in step three has an average number of layers of 1 to 2 layers and a thickness of 0.6 to 2.2 nm.
Citation Information
Patent Citations
Modified graphene oxide as well as preparation method and application thereof
CN110937598A
Aqueous drilling fluid composition comprising xanthan gum and an exfoliated 2d material
WO2022029311A1